The Impact of Environmental Factors and Emotional Disorders on Occupational Health Issues - Chaiprakarn, Somboon; Sakulthaew, Chanakarn; Siripipatthanakul, Supaprawat; Ratcha, Mongkol (Journal of Health Science and Alternative Medicine, 2024)
Introduction: This study investigates the relationship between factors such as age, gender (specifically male workers), alcohol and drug addiction, occupational risks, emotional disorders, and occupational health issues in the workplace. Methods: Data was collected through an online survey using convenience sampling from factory workers in Thailand (n=385). Descriptive analysis and Partial Least Squares Structural Equation Modeling (PLS-SEM) were employed to analyze the relationships among the variables. Results: The results indicate that emotional disorders significantly mediate the impact of alcohol and drug addiction, increasing age, occupational risks, and gender (male workers) on occupational health issues. Additionally, increasing age, alcohol and drug addiction, and occupational risks have a direct and significant effect on occupational illness or injuries in the workplace. However, the direct effect of gender (male workers) on occupational illness or injuries was not significant. Conclusions: Addressing emotional disorders, addiction, and occupational risks could help reduce occupational illnesses and injuries. Qualitative research should be implemented to gain deeper insights into these relationships.